Cleanliness as a Mirror of Faith: Ilmi's Interpretation of the Value of Cleanliness in the Qur'an and the Reality of Waste in Banten Society - Faidza, Haura Nadine Nayla; Wati, Putri Innayah; Khatimah, Lailatul; Ambarwati, Aisyah Mariful; Rosa, Andi (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
This study aims to analyze the values of cleanliness in the Qur'an with a scientific interpretation approach and relate it to waste management problems in Banten Province. The background of this research is based on the paradox between Islamic teachings that emphasize that cleanliness is part of faith (an-nadhafatu minal iman) and the fact that environmental cleanliness practices are still low in some Muslim societies. This research uses a descriptive qualitative method with a thematic interpretation approach (maudhu'i), which systematically examines the verses of the Qur'an related to cleanliness, both in physical and spiritual contexts. Data were collected through literature studies and analyzed to find the relevance of these verses in the context of waste management in the Banten community. The results of the study show that the Qur'an contains strong principles of environmental ethics, such as individual responsibility for cleanliness, the prohibition of making damage to the earth, and the importance of maintaining the balance of nature. The implementation of these values in social life can be a preventive and solution to the waste crisis that occurs. The conclusion of this study confirms that the integration of cleanliness values in the Qur'an into environmental policies and education is essential to build a sustainable clean culture. This research is classified as a Research Paper because it offers a scientific contribution based on the analysis of sacred texts associated with contemporary social problems.